A Descriptive Study to Assess the Knowledge Regarding Cardiac Rehabilitation among Cardiac Patients Admitted in Selected Hospital, Vadodara - S Patel, Ekta; Patel, Riddhi; Patel, Ruchita; Patel, Shefali; Solanki, Narendrasinh (International Journal of Psychosocial Rehabilitation, 2020)
Background of the study: Cardiac rehabilitation (secondary prevention programs) is reviewed as a standard of care and implements critically important treatment modalities for heightening the care of cardiac patients. Guidelines related to CR have stated that it is beneficial in patients who are undergoing various heart-related surgeries, i.e., coronary artery bypass grafting, coronary stent placement, and valve surgery. Implication of CR in these conditions proves advantageous clinical results. Involvement in CR has been shown to lessen morbidity and mortality in a worthwhile manner.Objectives of the study: The objectives of this study were to assess existing knowledge of patients regarding cardiac rehabilitation and to identify associations between knowledge scores and selected demographic variables.Material and method: An evaluative research approach with a descriptive research design was used. A total of 60 subjects were selected by using the purposive sampling technique. The samples were patients who had been diagnosed with cardiovascular disease. Participants were informed about the study, and written consent was taken prior to participation. The structured knowledge questionnaires were administered to assess knowledge regarding cardiac rehabilitation. The data was analyzed by using inferential and descriptive statistics.Result: While assessing the existing knowledge of patients regarding cardiac rehabilitation, the majority of patients show an inadequate knowledge level. Out of 60 patients, 63.33% had inadequate knowledge, and 36.67% had adequate knowledge. While assessing the association between knowledge score and selected demographic variables, there was no significant association between knowledge score and selected demographic variables. So H1 has failed to be accepted.Conclusion: The purpose of this study was to determine the awareness and to inspect the knowledge about existing knowledge regarding cardiac rehabilitation among patients. The study concluded that participants were having inadequate knowledge regarding cardiac rehabilitation and require health care professional aid to enhance their knowledge, improve quality of life, and decrease mortality rate due to cardiovascular disease.